Superconducting Thick-Films From a Y-Ba-Cu-O Precursor - Maurizio Sacchi; Fausto Sirotti; Bruno Morten; Maria Prudenziati (Active and Passive Electronic Components)
We have prepared screen-printed films of the Y-Ba-Cu-O compound starting from a spray-pyrolysis precursor powder. BeO ceramic substrates are confirmed to be inert with respect to the film up to about 1000ºC. Electrical properties of oxygen annealed films are investigated, evidencing excellent superconducting behaviour, both in terms of Tc(≃91K) and Jc (>102 A.cm-2 at 77 K).